Biometric characterization three population of semah mahseer Tor douronensis (Valenciennes, 1842) in support to conservation of genetic resources - Otong Zenal Arifin; Jojo Subagja; Wartono Hadie (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2015)
Semah mahseer populations are threatened due to the massive exploitation by fishermen, and disrupt the genetic diversity, thus resulting in the disruption of the natural population sustainability. The purpose of this study was to evaluate the genetic diversity semah mahseer from the Alas River, Mount Leuser, South East Aceh. This is the first step to maintaining a source of genetic diversity semah mahseer. Truss morphometric used to analyze the shape of the body that divides the body of the fish into the truss cell and the truss line. The results showed that the character of the three semah mahseer populations has an increasing internal diversity in the population - 1 to population-3 i.e. 62.5 %, 81.0 % and 85.7 % respectively. Population - 1 is a common form of all populations that showed the relationship between populations. Population - 2 received the sharing allele 25.0 % of the population - 1, and retained in the internal population of 81.0 % and 19.0 %, which is a common form of the population 1 and population- 2. Population-3 received the sharing allele 12.5% of the population - 1, and retained in the internal population of 85.7 % and 14.3%, which is a common form of the population-2 and population - 3. In general, genetic diversity increased from population-1 to population-3. Therefore population-3 is a potential candidate to be developed in the cultivation and conservation. Abstrak Ekploitasi berlebih ikan semah oleh para nelayan, merupakan ancaman terhadap populasi dan mengganggu keragaman genetik yang berakibat pada terganggunya kelestarian populasi ikan ini di alam. Penelitian ini bertujuan untuk mengevaluasi keragaman genetik populasi ikan semah yang berasal dari Sungai Alas, Gunung Leuser Aceh Tenggara sebagai upaya awal langkah yang dapat ditempuh untuk mempertahankan sumber keragaman genetik. Metode yang digunakan adalah analisis bentuk tubuh dengan truss morphometric, yang membagi tubuh ikan kedalam truss cell dan truss line. Hasil yang diperoleh menunjukkan bahwa karakter tiga populasi ikan semah dari Sungai Alas memiliki keragaman internal yang semakin meningkat dari populasi-1 hingga populasi-3 secara berturut-turut 62,5%; 81,0%; dan 85,7%. Ke-eratan hubungan antarpopulasi ditunjukkan oleh populasi-1 yang menjadi bentuk umum dari semua populasi. Populasi-2 menerima sharing allele sebesar 25% dari populasi-1 dan dipertahankan dalam populasi internalnya sebesar 81,0% dan 19,0% menjadi bentuk umum (common allele) dari populasi-1 dan populasi-2. Populasi-3 menerima sharing allele dari populasi-1 sebesar 12,5% dan dipertahankan dalam populasi internalnya sebesar 85,7% dan 14,3% menjadi bentuk umum dari populasi-2 dan populasi-3. Secara umum keragaman genetik semakin meningkat dari populasi-1 hingga po-pulasi-3. Dengan demikian populasi-3 dapat digunakan sebagai populasi kandidat untuk dikembangkan dalam budidaya dan konservasi.